The Impact Of Social Media On Consumer Shopping Habits Among Teenagers - Kartika Sari (PT. Anagata Sembagi Education, 2025)
The development of social media in the last decade has changed the consumption behavior of teenagers, with platforms such as Instagram, TikTok, and YouTube becoming the main space for forming opinions and lifestyles. Teenagers, as digital natives, are exposed to intense visual and audio-visual content curated by algorithms, which often form consumption standards based on social image, not functional needs. This phenomenon is further strengthened by the role of influencers who promote products through personal narratives that are often not recognized as advertisements. Teenagers tend to adopt impulsive consumption patterns due to social pressure and the strong influence of endorsements on social media, which further blurs the line between entertainment and marketing. This leads to faster and more emotional changes in shopping patterns, and encourages them to buy goods for social image. In addition, low digital and financial literacy among teenagers increases their vulnerability to manipulative marketing, which influences their purchasing decisions. This study aims to understand how social media, through influencers, influences teenagers' shopping habits, as well as the importance of digital and social literacy in helping teenagers make wiser and more rational consumption decisions. A descriptive qualitative approach is used to explore teenagers' consumption experiences, with a focus on understanding the impact of social media on developing consumption patterns.